Two Conceptions of Common-Sense Morality. (12th April 2016) - Krishna, Nakul
Abstract: Many moral philosophers tend to construe the aims of ethics as the interpretation and critique of 'common-sense morality'. This approach is defended by Henry Sidgwick in his influential The Methods of Ethics and presented as a development of a basically Socratic idea of philosophical method. However, Sidgwick's focus on our general beliefs about right and wrong action drew attention away from the Socratic insistence on treating beliefs as one expression of our wider dispositions. Understanding the historical contingency of Sidgwick's approach to ethics can help us reflect on whether there are other ways in which modern ethics can be Socratic.